2021
DOI: 10.1111/bcp.15135
|View full text |Cite
|
Sign up to set email alerts
|

The environmental impact of inhalers for asthma: A green challenge and a golden opportunity

Abstract: The propellants in metered‐dose inhalers (MDIs) are powerful greenhouse gases, which account for approximately 13% of the NHS's carbon footprint related to the delivery of care. Most MDI use is in salbutamol relievers in patients with poorly controlled disease. The UK lags behind Europe in this regard, with greater reliance on salbutamol MDI and correspondingly greater greenhouse gas emissions, roughly treble that of our European neighbours. There has been a broad switch towards MDIs in asthma treatment in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 49 publications
0
37
0
1
Order By: Relevance
“…13 The main reason behind the trend towards relying on MDIs in the UK is cost. 14 MDIs contain hydrofluorocarbon propellants which are powerful GHGs. For example, HFA-134a, which is found in most MDI inhalers, has a global warming potential of 1300.…”
Section: The Carbon Footprint Of Inhaler Prescribingmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The main reason behind the trend towards relying on MDIs in the UK is cost. 14 MDIs contain hydrofluorocarbon propellants which are powerful GHGs. For example, HFA-134a, which is found in most MDI inhalers, has a global warming potential of 1300.…”
Section: The Carbon Footprint Of Inhaler Prescribingmentioning
confidence: 99%
“…It has been reported that two-thirds of patients' day-to-day asthma treatment is dominated by a short-acting beta agonist MDI. 14 What this means is i There is a third option which involves developing alternatives which contain propellants with lower global warming potentials. This is an important option because there are patients who are not able to use a DPI and so having an MDI with a lower carbon footprint would be useful.…”
Section: The Carbon Footprint Of Inhaler Prescribingmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In addition to the individual patient harm associated with excess prescription of SABA, the pMDIs (pressurized Metered-Dose Inhalers) are a major contributor to healthcare associated carbon footprint, and thereby global warming. 16 Hence reducing SABA over-prescribing is important both for individuals and for global health.…”
Section: Introductionmentioning
confidence: 99%